Youth entrepreneurship in agribusiness in Indonesia - Xiobo Zhong; Srivastava, Nandita; Babu, Suresh Chandra (Syngenta Foundation, 2023)
Creating opportunities for youth is a necessary and important strategy to optimally harness the existing demographic dividend. Since agriculture sector continues to be an important resource in many developing countries including Indonesia, it is an important pathway to create employment opportunities for youth. The presence of a strong entrepreneurship ecosystem in the agribusiness sector can incentivize youth to consider participating in the sector. Indonesia has undertaken several steps in this direction which have propelled growing entrepreneurship opportunities, yet many challenges exist. Difficulty in accessing markets, financial constraints, poor access to credit, lack of adequate infrastructure, weather, pest and disease problems, and lack of available skills training are all contributing factors. There is a need for skilled human capital at different levels such as to provide i) advisory support on innovations and technical know-how and ii) well trained employees to help in running the business. Entrepreneurs must also emphasize on their role as mentors to train, encourage, and support other youth. This report is part of an international multi-country comparative study on youth entrepreneurship in the agribusiness sector. It uses a conceptual framework on key drivers of the success of youth entrepreneurship. Through a combination of a literature review of the status of the policy, institutional, technological, business, and individual environments that support youth entrepreneurship and case studies of agribusiness entrepreneurs, the report analyzes the existing agribusiness entrepreneurship ecosystem in Indonesia. Key lessons and recommendations are drawn with the aim to strengthen youth entrepreneurship in the agriculture sector.